EDUCATIONAL HEALTH TECHNOLOGY FOR GUIDANCE AND SUPPORT IN THE EPIDEMIOLOGICAL SURVEILLANCE OF EXOGENOUS INTOXICATIONS: AN EXPERIENCE REPORT (REMUNOM, 2025)
Exogenous intoxication represents a significant challenge for public health, requiring qualified responses from health services. This experience report describes the development of an educational booklet as a health technology to support teams in the epidemiological surveillance of exogenous intoxications in Maceió, Alagoas. The booklet was developed as part of the Multiprofessional Residency Program in Family Health at the State University of Health Sciences of Alagoas (UNCISAL), in partnership with the Municipal Health Department of Maceió. The material was structured into topics, covering everything from the definition and types of poisoning to diagnosis, treatment, notification and prevention, based on scientific evidence and local epidemiological data. The target audience is health professionals, especially in urgent and emergency services, with the aim of improving the identification of cases, the correct completion of notifications and the implementation of preventive actions. The booklet was developed in four stages: conception, structuring, theoretical content and layout. Analysis of data from the Notifiable Diseases Information System (SINAN) revealed a 57.7% reduction in notifications between 2019 and 2023, possibly due to underreporting. The main toxic agent identified was medication, with suicide attempts as the main motivation. The booklet appears as an accessible educational tool, capable of expanding knowledge and supporting professionals in the management and surveillance of exogenous intoxications, contributing to the qualification of health practices and the prevention of serious complications.